Organizational Culture as the Governance Architecture of Islamic Education Management: A Systematic Literature Review of Madrasah Studies (2017–2026) - Bustanul Arifin; Ulfi Naja Arsyada (Institut Agama Islam At-Tahdzib, 2025)
Islamic education management in madrasahs is increasingly confronted with complex challenges, including quality assurance, public accountability, and the need for innovation and adaptation to social and technological change. Within the academic literature, studies on madrasah management predominantly emphasize leadership, performance, and innovation, while organizational culture is often positioned as a secondary supporting factor. This article aims to map, analyze, and synthesize the development of organizational culture–based Islamic education management studies through a Systematic Literature Review (SLR) employing a narrative PRISMA approach. Literature searches were conducted using Google Scholar and the Garuda database (Indonesia) covering publications from 2017 to 2026. The synthesis reveals that most studies continue to treat leadership, organizational culture, and innovation as separate constructs, resulting in fragmented understandings of madrasah governance. The findings affirm that organizational culture should be positioned as the core governance architecture that bridges Islamic values with modern managerial practices. This article contributes by reconstructing organizational culture as an integrative foundation of Islamic education management and by offering theoretical, practical, and policy implications for strengthening sustainable madrasah governance.